A digital video system for the automated measurement of repetitive joint motion. - ChunMei Lu
Automated measurement and analysis of human motion during performance of workplace tasks are desirable for ergonomic studies. While numerous technologies exist for accurate measurement of biomechanical data, their use is often not feasible in the workplace environment. We present a digital-video based system suitable for measuring human motion of repetitive workplace tasks. Due to practical considerations, a single-camera solution is exploited by adding some control over the environment. We present an analysis of experiments demonstrating the accuracy of our system.
Keywords: Biomechanical data; Digital video system; Ergonomic study; Human motion measurement telemonitoring; Repetitive joint motion; Workplace environment